Investigating special education curriculum for visually impaired children in solving family adjustment issues in Pakistan - Malik, Shazia; Abdul Manaf, Umi Kalthom; Ahmad, Nor Aniza; Ismail, Maimunah (Human Resource Management Academic Research Society, 2017)
Purpose: The purpose of this research is to evaluate the curriculum with reference to special education for visually impaired children across Pakistan while solving their issues in family adjustment. In this study, family adjustment is a process through which a child, who by any means owns any disability attempts to adjust in his/her family through the moral and functional support of elders and siblings. This is a proven fact that Pakistan is one of those nations, which have the educational infrastructure for visually impaired children, yet it is still not entirely developed for visually impaired learners. Methodology: Data collected by self developed questionnaire about the problem under investigation from a sample of 5 secondary schools of visually impaired children aged 15-20 years old in Lahore, Pakistan. These students are selected through stratified sampling according to age, gender, and educational level. The instrument, namely survey on the educational satisfaction level was utilized to collect the data. The researcher used simple descriptive statistical techniques such as mean and percentages to analyze the collected data. Findings: Data showed that majority of visually impaired children were satisfied with the schools an educational system given to them. It is suggested that with the active participation of teachers can play a remarkable role in providing visually impaired children with provision of an effective learning environment to help them in adjusting in their families. Significance: The study brings to light the importance with benefits visually impaired children in nurturing their educational concerns to adjust them in their families. Moreover, this research is significant to visually impaired children, their parents, teachers.